CONDITION FACTOR AND ECOLOGY OF ENDOHELMINTHS IN Metynnis lippincottianus FROM THE CURIAÚ RIVER, IN EASTERN AMAZON (BRAZIL) - Abthyllane CARVALHO; Roger Leomar FERREIRA; Priscila ARAÚJO; Marcos TAVARES-DIAS; Edilson MATOS; Marcela Nunes VIDEIRA (Boletim do Instituto de Pesca)
Fish are among the vertebrate groups most susceptible to parasitic infections due to environmental characteristics that can favor the development of parasites; also, position of the host in food web has been associated with the parasitism. The aim of this study was to investigate the ecology of parasites endohelminth in Metynnis lippincottianus from the Curiaú River, in eastern Amazon (Brazil), as well as to evaluate the parasite-host interactions. From 110 specimens of M. lippincottianus examined, 76.3% were infected by one or more parasite species, and a total of 146 parasites such as Procamallanus (Spirocamallanus) inopinatus (Nematoda), larvae of Contracaecum sp. (Nematoda) and Neoechinorhynchus pterodoridis (Acanthocephala) were collected in intestine. However, the dominance was of nematode species, and the parasites had uniform or random dispersion. The parasitic infracommunities showed low Shannon-Wiener diversity (0.2 ± 0.3), low evenness (0.2 ± 0.3) and low species richness of parasites (1.1 ± 0.8). The abundance of Contracaecum sp. presented a weak positive correlation with the weight of hosts, and relative condition factor was not affected by the parasitism. This first study about parasites of M. lippincottianus from Curiaí River basin is the first report of N. pterodoridis for this host.